HUBUNGAN TANGGUNG JAWAB DAN DUKUNGAN KELUARGA TERHADAP RENCANA PEMBERIAN AIR SUSU IBU - Nindy Elliana Benly (NHM PRESS, 2021)
Quality human resources (HR) are an important element in the success of national development. Children as human resources who continue the nation and hope for the future, families, communities and countries need to be given guidance and direction as early as possible even from the womb. This guidance begins with paying more attention to pregnant women, so that they get adequate nutrition and are safe in carrying out the process of pregnancy and childbirth. After the baby is born, it is necessary to provide food that can ensure optimal physical and spiritual growth. Breast milk is the most suitable food for infants and has the highest nutritional value compared to human-made baby food or animal milk, such as cow's milk. This research is a quantitative research through analytical descriptive approach with the research method